Diagnostic and prognostic value of right ventricular eccentricity index in pulmonary artery hypertension. (1st April 2020) - Wang, Lili; Chen, Xiaoling; Wan, Ke; Gong, Chao; Li, Weihao; Xu, Yuanwei; Wang, Jie; He, Juan; Wen, Bi; Han, Yuchi; Zeng, Rui; Chen, Yucheng
Abstract : The right ventricle experiences dynamic changes under pressure overload in pulmonary artery hypertension. This study aimed to evaluate the diagnostic and prognostic value of right ventricular eccentricity index (RVEI) in pulmonary artery hypertension. A total of 100 pulmonary artery hypertension patients (mean age, 36.85 (SD, 13.60) years; males, 30.0%) confirmed by right heart catheterization and 147 healthy volunteers (mean age 45.58 (SD, 17.58) years; males, 42.50%) were enrolled in this prospective study. All participants underwent cardiac magnetic resonance imaging (MRI) examination, and balanced steady‐state free precession (bSSFP) cine sequences were acquired. RVEI was measured on short‐axis cine images at the mid‐ventricular level of the right ventricle in end systole. The study found that RVEI was significantly lower in pulmonary artery hypertension patients than in healthy volunteers (1.84 (SD, 0.40) vs. 2.46 (SD, 0.40); p < 0.001). In pulmonary artery hypertension patients, RVEI was correlated with log(NT‐proBNP) (r = −0.388; p < 0.001), right ventricular end‐diastolic volume index (r = −0.452; p < 0.001), right ventricular end‐systolic volume index (r = −0.518; p < 0.001), and right ventricular ejection fraction (r = 0.552; p < 0.001). RVEI could discriminate pulmonary artery hypertension patients from healthy volunteers with 91.8% sensitivity and 68.0% specificity. Over median follow‐up of 14.8 months (interquartile range: 6.7–26.9 months), RVEI was demonstrated to be an independent predictor for adverse outcome (HR = 0.076; 95% CI, 0.013‐0.458; p = 0.005). In conclusion, MRI‐derived RVEI appears to be a useful diagnostic and prognostic value in pulmonary artery hypertension, and it provides incremental value to risk stratification strategy.